Case report: Coxiella burnetii endocarditis in the absence of evident exposure - Bozza, Silvia; Graziani, Alessandro; Borghi, Monica; Marini, Daniele; Duranti, Michele; Camilloni, Barbara (Frontiers in Medicine, 2023)
Q fever is a worldwide zoonotic disease caused by Coxiella burnetii. In humans, it can manifest clinically as an acute or chronic disease and endocarditis, the most frequent complication of chronic Q fever is associated with the greatest morbidity and mortality. We report a severe case of endocarditis in a 55-year-old man with a history of aortic valve replacement affected by monoclonal gammopathy of undetermined significance (MGUS), and living in a non-endemic area for C. burnetii. After two episodes of fever of unknown origin (FUO), occurring 2 years apart and characterized by negative blood cultures, a serological diagnosis of Q fever endocarditis was performed even though the patient did not refer to possible past exposure to C. burnetii. Since people with preexisting valvular heart disease, when infected with C. burnetii, have reported a 40% risk of Q fever endocarditis, clinicians should maintain a high index of suspicion for infective endocarditis in all patients with FUO even when the exposure to C. burnetii appears to be unlikely.